Respuesta :

By the binomial theorem,

[tex]10^{2019}=(9+1)^{2019}=\displaystyle\sum_{n=0}^{2019}\binom{2019}n9^{2019-n}[/tex]

The last term in the sum, when [tex]n=2019[/tex], is

[tex]\dbinom{2019}{2019}9^{2019-2019}=1[/tex]

which is eliminated, leaving us with

[tex]10^{2019}-1=\displaystyle\sum_{n=0}^{2018}\binom{2019}n9^{2019-n}[/tex]

[tex]10^{2019}-1=\displaystyle\binom{2019}09^{2019}+\binom{2019}19^{2018}+\cdots+\binom{2019}{2018}9[/tex]

Each term in the remaining sum has a common factor of 9, so [tex]10^{2019}-1[/tex] must be composite.